Analisis Perbandingan Biaya Langsung (Direct Cost) dan Biaya Tidak Langsung (Indirect Cost) pada Pasien Stroke Di Rumah Sakit - Aulia, Destanul; Ayu, Sri Fajar; Ritonga, Nefonafratilova (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Stroke is divided into two categories, ischemic and hemorrhagic. Each year there are 15 million people around the world who suffer a stroke. Stroke treatment requires a high cost. The burden of heart disease and stroke from 2012 to 2030 reaches Rp. 1,7 trillion. This study aimed to analyze the comparison of direct and indirect costs of stroke patient in X hospital in 2017. The results showed that the number of ischemic stroke patients more than hemorrhagic stroke patients. The average cost of hemorrhagic stroke patients is greater at Rp 3,763,750 than the average cost of ischemic stroke patients. The total direct cost of stroke patients is Rp. 527,895,000 (54.7%) and the total indirect cost of Rp. 437,295,000 (45.3%). It is recommended that the public more actively to monitor health, blood pressure movements, and symptoms of stroke.